Hepatoprotective effects of ethanol extract of mobe leaves/eeml (artocarpus lacucha buch-ham.) against carbon tetrachloride induced hepatotoxicity in rats: English - Lubis, Meiva Amelia; Dalimunthe, Aminah; Sitorus, Panal; Satria, Denny (International Journal of Ecophysiology, 2024)
This study evaluates the protective effects of ethanol extract of mobe leaves (Artocarpus lacucha Buch-Ham.) on ALT, AST, and bilirubin levels in rats induced with carbon tetrachloride (CCl4) on Liver. The ethanol extract was prepared by maceration using 96% ethanol. Results showed that administering 400 mg/kg BW of the extract significantly reduced total bilirubin, ALT, and AST levels in CCl4-induced rats. Phytochemical screening revealed bioactive compounds like flavonoids, alkaloids, tannins, saponins, triterpenoids, and glycosides, which are potential antioxidants and hepatoprotective agents. The study concludes that mobe leaf extract has potential as a therapeutic agent to protect the liver from toxic damage. The significant contribution of this research is providing a scientific basis for using mobe leaf extract as a natural hepatoprotective agent, highlighting its potential for safe and effective herbal medicine. Further research and clinical trials are recommended.